Modelling and performance analysis of the BVP M-80A hybrid drive - Milićević, Stefan; Muždeka, Slavko (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction: Hybrid technology has been successfully incorporated into the industry of passenger and commercial vehicles. Driven by the success and benefits that hybrid technology brings, many defense organizations around the world invest in the development of hybrid technology for combat vehicles and develop prototypes of tracked combat vehicles which have lower fuel consumption, better performance, better exhaust emission, and additional onboard electric power. However, various technical challenges must be resolved before it comes to the introduction of hybrid tracked combat vehicles in operational use. Several successful tests of prototypes have been conducted so far, but there are still restrictions on key technologies such as electric motors, electronics, and storage of electricity. In such conditions, where finance is limited, mistakes cannot be allowed nor spending a lot of resources on planning, building prototypes, and testing. Method: Therefore, it is clever to run the simulation software with which it is possible to examine various parameters in simulated conditions which more or less mimic real operating conditions. This paper aims to show one of possible solutions concerning the selection of appropriate technologies of hybrid drive, to propose a system solution for a hybrid BVP M80A, and to display a simulation hybrid drive model and the results obtained from the model devised in Simulink. Results: The results obtained by the simulation show that the proposed hybrid drive solution provides better performance while retaining key drivetrain elements of the vehicle. Conclusion: Only turning parameters are considered during the simulation but it is clear that the hybrid drivertrain has advantages related to straight-line motion as well. Also, sound projections about the drivetrain performance and control can be made with the use of the proposed model.